ANALYSIS OF THE ROLE OF PEER TEACHING IN THE PROCESS OF COUNSELING EDUCATION AND TEACHING - Julkarnaen, Julkarnaen; Zakaria, Alif Muhammad (The Pontianak State Institute of Islamic Studies, 2024)
Peer teaching and peer counseling are methods and approaches that can be used in an educational context to enhance the teaching and learning process and provide emotional and social support to students. Peer learning can increase student motivation, social skills, understanding of material, problem-solving skills, and self-confidence. Students learn interactively and mutually support each other, and can get explanations that are easier to understand from classmates who are more experts in certain fields. This study uses the literature study method with a qualitative data approach. The results of the research show that peer learning and peer counseling can be effective approaches in improving the teaching and learning process and providing support to students. Continuous evaluation needs to be done to improve the quality and effectiveness of the implementation of the two methods.